Using Genetic and Ant Colony Algorithms to Address the Security Issues in Cloud Computing-Based Accounting Systems - AlFarttoosi, Dawood Salman; Kadhim, Abdalabbas Hassan (International Journal of Psychosocial Rehabilitation, 2020)
: Due to the recent substantial development in the digital world, transfer data over the network has become more and more critical issue in the context of cloud computing-based accounting systems. This paper discusses the main security mechanisms that could be implemented to fulfill the data protection and confidentiality in cloud computing-based accounting systems. The findings assert the ability to use the computational intelligence techniques (Genetic and Ant colony) to build trust environment in cloud computing. Genetic proposed to apply the Cryptography and achieve data encryption, whereas Ant algorithm combined to add the complexity by creating strong path for each cloud user and this would enable the system to easily detect the unauthorized such as hackers when they try to reach and hack the data.